3D Modelling of Ground Surface Vibration Induced by Underground Train Movement. (2017) - Singh, D.V.; Seth, Y.
Abstract: Correia et al. [1], developed an expression to model the force distribution due to axle loads, with respect to the moving referential. The above force distribution was used for Finite Element Analysis using PLAXIS 3D. A code is developed in MATLAB to generate a matrix of dynamic multipliers for each static point load applied along the railway track with each time step. The amount of load applied is equal to the axle load of the train resulting from the solution of the Winkler Beam for the movement of a load. The results can be used for gauging the effect of changing various geological and physical parameters on the distribution of force due to axle load. Once calibrated to geotechnical and physical data corresponding to sites above actual underground train tracks, the model can be used to predict the effect of vibrations on existing infrastructure.